Pairing and Coherence Transition in La1.82Sr0.18CuO4 Strongly Two-Dimensional Superconductor - D. A. Landínez Téllez (Brazilian Journal of Physics, 2006)
We report conductivity fluctuation measurements in the La1:82Sr0:18CuO4 high temperature superconductingmaterial. The conductivity fluctuation analysis was performed by utilizing the concept of the logarithmic derivativeof the conductivity excess. Close and above the critical temperature Tc, we experimentally determine theoccurrence of Gaussian and critical fluctuation regimes. Systematic measurements of conductivity as a functionof temperature were performed for several values of transport current j. Fluctuation analysis close to the zero resistivitytemperature Tc0 was performed and we clearly identified a characteristic exponent, which is analyzed bythe dynamical scaling theory and considering a percolation-like transition in a frustrated and disordered system.The observation of a glass-like behavior in our experiments permits to interpret our results as corresponding toa vortex-glass regime.